Exploration of the molecular mechanism of melatonin against polycystic ovary syndrome based on a network pharmacology approach and experimental validation - Cheng, Ran; Zhu, Ying; Wang, Sheng-kai; Zong, Chun-Xiao; Zhao, Hong-Li; Zhang, Qin (Frontiers in Endocrinology, 2025)
BackgroundAmong women of childbearing age, polycystic ovary syndrome (PCOS) is the predominant etiology of anovulatory infertility. Recent research has elucidated the role of melatonin as a medicinal agent in PCOS, especially hyperandrogenism. However, the precise mechanisms underlying its therapeutic efficacy remain largely unknown. This study integrated network pharmacology, molecular docking, molecular dynamics simulations, and laboratory confirmation to explore the pharmacological mechanisms of melatonin in PCOS.MethodsFirst, we conducted animal studies to evaluate the therapeutic efficacy of melatonin by administering it to circadian disruption-induced PCOS-like rats. Prospective medicinal targets of melatonin were acquired from databases such as DrugBank, Traditional Chinese Medicine Systems Pharmacology, PharmMapper, and SwissTarget Prediction. Targets related to PCOS were extracted from three databases: DisGeNET, GeneCards, and the National Center for Biotechnology Information gene. To visualize the relationships between proteins, a protein-protein interaction network was generated using the STRING database. Further investigation of these targets involved analyzing protein-protein interaction networks and conducting GO/KEGG enrichment analysis. Molecular docking techniques were employed to examine the interactions between melatonin and crucial targets. Molecular dynamics simulations were performed to confirm the stability of the association between the hub targets and the melatonin ligand. Finally, animal studies validated the effect of melatonin on the identified targets.ResultsAnimal experiments showed that melatonin ameliorated hyperandrogenism and ovarian dysfunction in constant darkness-induced PCOS-like rats. Network pharmacology analysis demonstrated that melatonin exhibited multiple modulatory effects on circadian rhythm, reproductive processes, metabolic processes, and oocyte maturation. Cytoscape network analysis revealed seven key targets, of which AR and CYP19A1 showed the highest affinity for melatonin by molecular docking. The stability of the AR/CYP19A1-melatonin complex was verified through computational simulations using molecular dynamics techniques. Furthermore, animal experiments have validated that melatonin can regulate key genes associated with hyperandrogenism, including AR and CYP19A1.ConclusionThrough network pharmacology, molecular docking, and experimental validation, this study reveals how melatonin may ameliorate PCOS and hyperandrogenism. Results suggest melatonin’s effects involve androgen excess mitigation, though further validation is needed. This work provides insight into melatonin’s actions in circadian-associated PCOS.